Multiple large pancreaticoduodenal artery aneurysms due to celiac artery occlusion: Combination of the aorto-hepatic bypass and coil embolization with a dual approach through both the superior mesenteric artery and bypass - Kengo Ohta, MD; Masashi Shimohira, MD; Jumpei Shoji, MD; Shiro Yoshida, MD; Taku Takaishi, MD; Mamoru Morimoto, MD; Yoichi Matsuo, MD; Tatsuhito Ogawa, MD; Hisao Suda, MD; Yuta Shibamoto, MD (Radiology Case Reports, 2021)
Pancreaticoduodenal artery aneurysm can occur from occlusion or stenosis of the celiac artery due to arteriosclerosis or median arcuate ligament compression. The risk of rupture of the aneurysm is independent of the aneurysmal diameter. A 78-year-old woman presented with multiple large aneurysms of the anterior superior pancreaticoduodenal artery. To preserve arterial flow to the liver, bypass grafting from the supra-celiac aorta to the common hepatic artery was performed at first. Coil embolization was successfully performed 10 days later with a dual approach through both the superior mesenteric artery and bypass. It was considered that the combination of the aorto-hepatic bypass and coil embolization was effective for the pancreaticoduodenal artery aneurysms due to celiac artery occlusion.